Effectivity of Carrot (Daucus carota) Seed Oil as Hair Growth Promoter on Rats (Rattus novergicus) - Andriyanto, Andriyanto; Aurelia, Sharon; Zylviana, Tengku; Natalie, Gabriela; Putra, Hamdika Yendri (Faculty of Medicine, Universitas Padjadjaran, 2024)
Hair quality and health are important not only for the esthetical reasons but also to maintained the hair’s function in protecting the head. Carrot seed oil (CSO) is rich in vitamin A and beta-carotene, which influence hair quality. CSO also contains carotol, which has anti-fungal properties that treat dandruff. This research aimed to observe the potential of CSO as a hair growth promoter. Twenty male rats were used in the study, with their backs shaved and divided into two areas, each with different frequencies of CSO application. The backs of the rats were given CSO every day for 14 consecutive days with different concentrations, i.e., 25%, 50%, and 75%. Hair growth was assessed based on its length, root, shaft, and tip thickness on days 9,12, and 14 and the results were recorded. On day 15, the rats were euthanized and their skin was collected to observe the number of follicles. Results showed that the application of CSO with different concentrations had no effect on hair length growth but it did affect the thickness of the root, shaft, and tip of the hair, with the best concentration being 75%. The frequency of application did not seem to affect the growth in terms of the length or thickness of the root, shaft, and tip of the hair; however, the application of CSO with 75% concentration and an application frequency of once a day produced the best amount of follicle regeneration.